2014
DOI: 10.1002/jbm.a.35284
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial adhesion to poly-(d,l)lactic acid blended with vitamin E: Toward gentle anti-infective biomaterials

Abstract: Anti-infective properties of biomedical materials are often achieved by loading or coating them with powerful bactericides. Undesirably, these bioactive molecules can damage the host cells at the biomaterial-tissues interface and, sometimes, even determine systemic toxic effects. The search for biomaterials able to actively resist infection while displaying a safe cytocompatibility profile toward eukaryotic cells is being progressively developed. Poly-(D,L)lactic acid (PLA) is a broadly used resorbable materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 48 publications
2
18
0
Order By: Relevance
“…It was demonstrated that the inclusion of tocopherol in PE significantly decreased the adhesion ability of St. epidermidis, St. aureus, and E. coli. A similar anti-biofilm action of tocopherol against St. epidermidis and St. aureus has also been observed when it is included in polylactic acid [32]. Although there is a generally accepted lack of antibacterial activity of tocopherol, some studies have demonstrated such activity against St. epidermidis, St. aureus, E. coli, and Ps.…”
Section: Adenosine Triphosphate Bioluminescencementioning
confidence: 62%
“…It was demonstrated that the inclusion of tocopherol in PE significantly decreased the adhesion ability of St. epidermidis, St. aureus, and E. coli. A similar anti-biofilm action of tocopherol against St. epidermidis and St. aureus has also been observed when it is included in polylactic acid [32]. Although there is a generally accepted lack of antibacterial activity of tocopherol, some studies have demonstrated such activity against St. epidermidis, St. aureus, E. coli, and Ps.…”
Section: Adenosine Triphosphate Bioluminescencementioning
confidence: 62%
“…Using an animal model, it was demonstrated that vitamin E could play a key role in enhancing host protection against Heligmosomoides polygyrus . Vitamin E was also shown to decrease bacterial adhesion and biofilm accumulation on the surface of vitamin E‐blended polymers . These data highlight the potential of vitamin E against periodontal bacteria and such virulence factors as LPS.…”
mentioning
confidence: 88%
“…Intrinsically bioactive materials or doped/blended/coated biomaterials with antibacterial substances are being progressively developed and optimized, as the new generation of gently anti-infective biomaterials , i.e. , materials that, besides being safe for eukaryotic cells and anti-infective towards bacteria, are also endowed with anti-inflammatory potential or other beneficial biological properties [88,89]. For the orthopaedic implants, the anti-infective materials should be designed to be able to oppose bacterial colonization and, at the same time, to support tissue repair [9].…”
Section: Biomaterials Biofilms and Neutrophilsmentioning
confidence: 99%